2017
DOI: 10.1002/jsfa.8291
|View full text |Cite
|
Sign up to set email alerts
|

Determination of two potential toxicity metabolites derived from the disruption of the pksCT gene in Monascus aurantiacus Li As3.4384

Abstract: Maximum MPA and MPB yields (2073.7 and 1961.7 µg g , respectively) were observed after 16 days of cultivation. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Therefore, methods to reduce citrinin production by Monascus have been studied. The most powerful technology to produce a citrinin non-producing mutant is to rely on genetic engineering (Huang et al, 2017, Liang et al, 2018. In fact, the loss of function of citS involved in the first step of the reaction of citrinin production leads to the complete elimination of citrinin production (He et al, 2013) However, in the field of food industry, classical mutagenesis using mutagens has been an effective technique to improve microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, methods to reduce citrinin production by Monascus have been studied. The most powerful technology to produce a citrinin non-producing mutant is to rely on genetic engineering (Huang et al, 2017, Liang et al, 2018. In fact, the loss of function of citS involved in the first step of the reaction of citrinin production leads to the complete elimination of citrinin production (He et al, 2013) However, in the field of food industry, classical mutagenesis using mutagens has been an effective technique to improve microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of citS resulted in the complete elimination of citrinin production in M. purpresus (He et al, 2013). Thus, the construction of citrininnonproducing Monascus strains using gene recombinant technology is a powerful tool (Huang et al, 2017;Liang et al, 2018), although using classical mutagenesis might be more favorable for use in the fermented food industry.…”
Section: Introductionmentioning
confidence: 99%
“…To remove citrinin from Monascus products, several methods, screened for low or no production of citrinin from Monascus strains and a lack of mutagenesis and gene transformation of Monascus, have been developed in the last several decades. [22][23][24][25][26][27] In our previous study, we found that some flavonoids can affect the production of citrinin by Monascus. 28 Soybean isoflavones (SI) are flavonoids whose main components include daidzein, genistein, soybean flavin, and flavin glycoside.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, methods to reduce the citrinin content of Monascus products have attracted great attention in Monascus ‐related research. To remove citrinin from Monascus products, several methods, screened for low or no production of citrinin from Monascus strains and a lack of mutagenesis and gene transformation of Monascus , have been developed in the last several decades …”
Section: Introductionmentioning
confidence: 99%
“…There are two main sources of citrinin residues: (1) Monascus -contaminated soybeans, sorghum, rice, oats, and related products [11]; (2) citrinin is often contaminated in red yeast products that contain pigments, since the citrinin and pigments have a concomitant relationship. The safety of Monascus products has attracted worldwide attention due to the existence of citrinin [12,13].…”
Section: Introductionmentioning
confidence: 99%